2014
DOI: 10.1111/jpim.12188
|View full text |Cite
|
Sign up to set email alerts
|

CEOs’ Transformational Leadership and Product Innovation Performance: The Roles of Corporate Entrepreneurship and Technology Orientation

Abstract: Product innovation is an important research topic that has stimulated significant interest among management scholars and practitioners. Leadership has been suggested to be a critical factor affecting product innovation. Numerous studies have documented that transformational leadership positively influences product innovation performance, which is conceptualized as the degree to which a new product and/or service has achieved its market share, sales, rates of asset return, rates of investment return, and profit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
205
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 234 publications
(237 citation statements)
references
References 86 publications
(114 reference statements)
9
205
0
1
Order By: Relevance
“…Transformational and charismatic leadership through inspiration, vision and deeper meaning may promote incremental contributions (Burns, 1978) and have been linked to organizational performance (Frese and Gielnik, 2014), innovations (Kraft and Bausch, 2016) and team decision-making skills (Dionne et al, 2004;Zhou et al, 2017). Chen et al (2014) recently found that this kind of leadership exerts an influence on product innovation and ultimately on corporate entrepreneurship. Charismatic leadership behaviour has been shown to exert a positive impact on a wide range of individual and organizational outcomes in a variety of contexts, including military (Bass et al, 2003;Hardy et al, 2010), business (Barling et al, 1996;Ensley et al, 2006;Jung et al, 2003), public sector (Rafferty and Griffin, 2004) and education (Koh et al, 1995).…”
Section: Leadership and Entrepreneurshipmentioning
confidence: 99%
“…Transformational and charismatic leadership through inspiration, vision and deeper meaning may promote incremental contributions (Burns, 1978) and have been linked to organizational performance (Frese and Gielnik, 2014), innovations (Kraft and Bausch, 2016) and team decision-making skills (Dionne et al, 2004;Zhou et al, 2017). Chen et al (2014) recently found that this kind of leadership exerts an influence on product innovation and ultimately on corporate entrepreneurship. Charismatic leadership behaviour has been shown to exert a positive impact on a wide range of individual and organizational outcomes in a variety of contexts, including military (Bass et al, 2003;Hardy et al, 2010), business (Barling et al, 1996;Ensley et al, 2006;Jung et al, 2003), public sector (Rafferty and Griffin, 2004) and education (Koh et al, 1995).…”
Section: Leadership and Entrepreneurshipmentioning
confidence: 99%
“…Secondly, corporate entrepreneurship, the older sister of SE has been previously shown to be linked to performance [50] and PIP [66]. The seminal work of [67] paved the way for later researchers, including [68], to devise the now prominent entrepreneurial orientation construct and its 9-item measurement scale.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…The contradiction of the results with empirical evidence is with HR flexibility. Here, for instance, Chen et al (2014) found that HR management practices affect product innovation performance of the company. Preenen et al (2017) focus on internal labor flexibility and confirmed the relationship between internal labor flexibility and product innovation.…”
Section: Product Innovation As Outcomementioning
confidence: 99%